The fourth international workshop on neutrino oscillations and their origin : (World Scientific, 2004)
The discovery of neutrino oscillations in 1998 initiated efforts to form a group to work on the detailed study of the phenomenon; this study is now supported by a grant-in-aid in the specific field of neutrinos from the Japanese Ministry of Education, Culture and Sports. The aim of this working group is to put together the efforts from various fields necessary for understanding neutrino oscillations in detail from both the experimental and the theoretical point of view. The 4th International Workshop on Neutrino Oscillations and Their Origin was held to discuss recent progress in both experimental and theoretical study.